Red Maca (Lepidium meyenii), a Plant from the Peruvian Highlands, Promotes Skin Wound Healing at Sea Level and at High Altitude in Adult Male Mice - Nunez, D (2017)
Wound healing consists of three simultaneous phases: inflammation, proliferation, and remodeling. Previous studies suggest that there is a delay in the healing process in high altitude, mainly due to alterations in the inflammatory phase. Maca (Lepidium meyenii) is a Peruvian plant with diverse biological properties, such as the ability to protect the skin from inflammatory lesions caused by ultraviolet radiation, as well as its antioxidant and immunomodulatory properties. The aim of this study was to determine the effect of high altitude on tissue repair and the effect of the topical administration of the spray-dried extract of red maca (RM) in tissue repair. Studies were conducted in male Balb/c mice at sea level and high altitude. Lesions were inflicted through a 10 mm-diameter excisional wound in the skin dorsal surface. Treatments consisted of either (1) spray-dried RM extract or (2) vehicle (VH). Animals wounded at high altitude had a delayed healing rate and an increased wound width compared with those at sea level. Moreover, wounding at high altitude was associated with an increase in inflammatory cells. Treatment with RM accelerated wound closure, decreased the level of epidermal hyperplasia, and decreased the number of inflammatory cells at the wound site. In conclusion, RM at high altitude generate a positive effect on wound healing, decreasing the number of neutrophils and increasing the number of macrophages in the wound healing at day 7 postwounding. This phenomenon is not observed at sea level.